2017
DOI: 10.1128/msphere.00193-17
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of Cerebral Malaria Patients Reveals Distinct Pathogenetic Processes in Different Parts of the Brain

Abstract: The pathophysiology and molecular mechanisms underlying cerebral malaria (CM) are still poorly understood. Recent neuroimaging studies demonstrated that brain swelling is a common feature in CM and a major contributor to death in pediatric patients. Consequently, determining the precise mechanisms responsible for this swelling could open new adjunct therapeutic avenues in CM patients. Using an MRI scanner with a higher resolution than the ones used in previous reports, we identified two distinct origins of bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 36 publications
2
91
0
Order By: Relevance
“…Indeed, a strong association between vasogenic edema (i.e. disruption of the blood-brain barrier - BBB) and brain swelling was found in all patients in that cohort, whereas only 5 out of 11 patients showed concomitant ischemia and cytotoxic edema [3]. Although brain endothelial activation and dysfunction are traditionally associated with CM the underlying mechanisms causing BBB disruption during CM are still not well defined.…”
mentioning
confidence: 99%
“…Indeed, a strong association between vasogenic edema (i.e. disruption of the blood-brain barrier - BBB) and brain swelling was found in all patients in that cohort, whereas only 5 out of 11 patients showed concomitant ischemia and cytotoxic edema [3]. Although brain endothelial activation and dysfunction are traditionally associated with CM the underlying mechanisms causing BBB disruption during CM are still not well defined.…”
mentioning
confidence: 99%
“…In addition, the analysis should be extended to other brain regions as well. A recent study demonstrated occipital lobe and basal ganglia to be significantly affected in CM . Inclusion of such brain regions in the analysis will provide a wider landscape of altered brain proteome upon CM.…”
Section: Resultsmentioning
confidence: 99%
“…Neuroimaging studies have demonstrated swelling of brain as a common feature in CM, which is a major contributor to death in pediatric cases. A recent study employed magnetic resonance imaging of CM patients and identified swelling of occipital/parietal and basal ganglia . Studies in mouse models using Plasmodium berghei ANKA strains have been suggestive of a few pathogenetic mechanisms; however, there has been no clear understanding of mechanisms involved in its clinical progression…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the latter feature, the reversible multifocal cerebral vasoconstriction usually seen in cases of RCVS has also been identified in more than 85% of patients with PRES. 17 Mohanty et al 18 reported that in 40.7% of patients with nonfatal cerebral malaria, brain MRI indicated findings of PRES or PRES-like vasogenic edema. Although RCVS was not described in this literature, it, like PRES, may be associated with cerebral malaria.…”
Section: Discussionmentioning
confidence: 99%